Factor the following problem: 12x² + 8x

Factorization of 12x² + 8x: Both components of the equation have a greatest common factor of 4x, meaning the factored equation is 4x(3x + 2).

Question

Asked 11/25/2014 6:49:20 PM

Updated 11/25/2014 9:46:34 PM

1 Answer/Comment

s

Rating

8

Factorization of 12x² + 8x:

Both components of the equation have a greatest common factor of 4x, meaning the factored equation is 4x(3x + 2).

Both components of the equation have a greatest common factor of 4x, meaning the factored equation is 4x(3x + 2).

Added 11/25/2014 9:46:34 PM

This answer has been confirmed as correct and helpful.

Select the difference of (8x^2 - 3x^3) - (2x^2 - 5x^3) **Weegy:** (2x^2 - 3x^3) - (8x^2 - 5x^3)
= (2x^2 - 3x^3) + (-8x^2 + 5x^3)
= 2x^3 - 6x^2 **User:** Simplify the following expression. 2(8x + 2) **Weegy:** 2(8x + 2) = (2)(8x) + (2)(2) = 16x + 4 **User:** Select the product of (5x - 4)(5x + 9). (More)

Question

Updated 11/20/2014 1:01:14 PM

3 Answers/Comments

(5x - 4)(5x + 9)

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

Added 11/20/2014 5:42:20 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/20/2014 8:52:32 AM], Rated good by andrewpallarca

-7w^3 + 6w^2 - 9w - 21w^2 + 18w - 27 **Weegy:** -7w^3 + 6w^2 - 9w - 21w^2 + 18w-27
= (-7w^3) + (6w^2 + -21w^2) + (-9w + 18w) + (-27)
= -7w^3 - 15w^2 + 9w - 27 (More)

Question

Expert Answered

Updated 11/28/2014 1:56:52 AM

0 Answers/Comments

Select the product of (-6x7y)(x3y5)

Question

Not Answered

Updated 11/24/2014 6:08:25 AM

1 Answer/Comment

(-6x^7y)(x^3y^5)

= -6x^7*x^3*y^5*y

= -6x^10y^6

= -6x^7*x^3*y^5*y

= -6x^10y^6

Added 11/24/2014 6:08:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/28/2014 1:57:22 AM], Rated good by andrewpallarca

Select the product of (5x - 4)(5x + 9).
25x2 - 25x - 36
50x - 36
25x2 + 25x - 36
10x + 5 **Weegy:** (5x + 1)? **User:** Select the product of (5x - 4)(5x + 9).
a. 25x2 - 25x - 36
b. 50x - 36
c. 25x2 + 25x - 36
d. 10x + 5 **Weegy:** (5x + 1)? **User:** (x + 4)3 (More)

Question

Updated 11/23/2014 11:37:33 PM

2 Answers/Comments

(5x - 4)(5x + 9)

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

Added 11/23/2014 11:34:57 PM

This answer has been confirmed as correct and helpful.

Rated good by andrewpallarca, Confirmed by andrewpallarca [11/24/2014 2:10:54 AM]

(x + 4)^3

= (x + 4)(x + 4)(x + 4)

= (x^2 + 8x + 16)(x + 4)

= x^3 + 8x^2 + 16x + 4x^2 + 32x + 64

= x^3 + 12x^2 + 48x + 64

= (x + 4)(x + 4)(x + 4)

= (x^2 + 8x + 16)(x + 4)

= x^3 + 8x^2 + 16x + 4x^2 + 32x + 64

= x^3 + 12x^2 + 48x + 64

Added 11/23/2014 11:37:33 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/24/2014 2:11:40 AM], Rated good by andrewpallarca

the product of (3x - 9)(3x - 9).

Question

Not Answered

Updated 11/24/2014 6:52:32 AM

1 Answer/Comment

(3x - 9)(3x - 9)

= 3x*3x - 9*3x - 3x*9 + (-9)*(-9)

= 9x^2 - 27x - 27x + 81

= 9x^2 - 54x + 81

= 3x*3x - 9*3x - 3x*9 + (-9)*(-9)

= 9x^2 - 27x - 27x + 81

= 9x^2 - 54x + 81

Added 11/23/2014 11:33:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/24/2014 6:52:27 AM]

34,439,953

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 498 [Total 6371] Ratings 9 Comments 408 Invitations 0 Offline

There are no comments.